Development of General Arithmetic E-Module Based on APOS Theory to Improve Problem Solving Ability and Independence in Middle School and High School Students - Resa Septian Aditya; YL Sukestiyarno; Adi Nur Cahyono (Universitas PGRI Semarang, 2023)
To learn about other parts of math, like how to work with numbers, you need to know arithmetic. The characteristics and concepts in mathematics are interrelated, therefore students need to acquire an introductory or basic grasp to assist in developing math skills (even if operations are considered basic stuff). This comprehension lays the groundwork for the acquisition of other mathematical talents, including problem-solving skills, which are crucial to a kid's success in school. Students and teachers alike rely heavily on online resources, yet this resource is not fully utilized in today's educational systems. In addition, not all online e-modules meet the standards of good e-modules, which results in subpar learning and makes it harder to accomplish certain educational goals. The goal of this research is to create an expert-based, user-friendly, and practical e-module for teaching elementary school mathematics that incorporates APOS theory in order to improve students' ability to learn independently and solve problems. This type of research is Design Research with the type of development studies divided into three phases, namely Preliminary research, Development or prototyping phase, and Assessment phase. Students from SMP Negeri 1 Winong, and MA Darul Ma'la made up the research sample. The data was gathered through a combination of tests, questionnaires, interviews, and observations. The study's findings demonstrate that the generated e-modules are of sufficient quality in terms of being valid, practical, and effective. validated by material experts and media experts, including lecturers and teachers, so that this e-module is considered valid by material experts and media experts, practical by lecturers, teachers, and students who use it through questionnaires, and effective based on problem-solving abilities and student learning independence after implementation.